Locust infestations and individual school dropout: Evidence from Africa - Abigail O. Asare; Bernhard Christopher Dannemann; Erkan Gören (University of Oldenburg, Department of Economics, 2023)
This paper examines the effect of desert locust infestations on school enrollment of children and young adults between 3 and 24 years of age. We combine individual and household survey data from the 2005-2019 Demographic and Health Surveys (DHS) Program with data on the spatial distribution of locust events in Africa. We show that months of exposure to locust infestations have a negative and statistically significant impact on individual schooling status. We find that individuals from farming households are affected more negatively by locust infestations than individuals from non-farming households. We also find that individuals from poorer farming households have a higher school dropout rate than individuals from wealthier farming households, highlighting the role of negative income shocks as a possible transmission mechanism for the effects of desert locust events. Our results also show that the estimated effect is amplified by the household's head educational status. A series of additional robustness tests further corroborate our main findings. We provide a quantitative assessment of the impact of a permanent 1.5 °C rise in global temperature on the frequency of locust events and possible implications for schooling outcomes over time. The results show that a 1.5 °C rise in temperature will decrease accumulated years of schooling by about 1.2 years over a period of 10 years.
Keywords: I21; O12; Q54; 330; Desert Locust; Demographic and Health Surveys (DHS) Program; School Enrollment; Income Shocks; Current Schooling; Farmers; Africa